2021
DOI: 10.3389/fmicb.2021.729307
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of LytM Protein Functions in Polar Elongation and Cell Division of Agrobacterium tumefaciens

Abstract: LytM-domain containing proteins are LAS peptidases (lysostaphin-type enzymes, D-Ala-D-Ala metallopeptidases, and sonic hedgehog) and are known to play diverse roles throughout the bacterial cell cycle through direct or indirect hydrolysis of the bacterial cell wall. A subset of the LytM factors are catalytically inactive but regulate the activity of other cell wall hydrolases and are classically described as cell separation factors NlpD and EnvC. Here, we explore the function of four LytM factors in the alphap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…Considering the possibility that depletion of PBP1a somehow signals for these phenomena, we decided to look at RgsM, another enzyme required for polar elongation. Previous work points to RgsM activity being required for incorporation of nascent PG by PBP1a [17]. However, depletion of RgsM did not cause surface spreading (Fig 1A) indicating that an imbalance of PG hydrolysis and synthesis triggers spreading and the inability pellet in A. tumefaciens .…”
Section: Resultsmentioning
confidence: 67%
“…Considering the possibility that depletion of PBP1a somehow signals for these phenomena, we decided to look at RgsM, another enzyme required for polar elongation. Previous work points to RgsM activity being required for incorporation of nascent PG by PBP1a [17]. However, depletion of RgsM did not cause surface spreading (Fig 1A) indicating that an imbalance of PG hydrolysis and synthesis triggers spreading and the inability pellet in A. tumefaciens .…”
Section: Resultsmentioning
confidence: 67%
“…Originally identified in enzymes that degrade bacterial cell wall, LysM domain is involved in peptidoglycan binding (Buist et al, 2008; Mesnage et al, 2014). LytM domain‐containing proteins have been found in a wide variety of bacteria and have been implicated in an array of important cellular processes such as cell elongation, division, and sporulation (Figueroa‐Cuilan et al, 2021; Peters et al, 2013; Uehara et al, 2009). Searching in SignalP 5.0 (https://services.healthtech.dtu.dk/service.php?SignalP-5.0) further confirmed the putative signal sequence in the N‐terminus of BB0761.…”
Section: Resultsmentioning
confidence: 99%
“…The M23 peptidases family comprises primarily endopeptidases that degrade bacterial peptidoglycans (Figueroa‐Cuilan et al, 2021; Vermassen et al, 2019). This family is further divided into two subfamilies, M23A and M23B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In distant organisms such as cyanobacteria, DipM was also found to be involved in cell separation, and is even conserved in chloroplasts of some algae, where it also allows division through PG digestion (Miyagishima et al, 2014). More recently, it has been shown that the homolog of DipM in Agrobacterium tumefaciens (DipM At ) is likely to have broader functions than just the direct hydrolysis of PG to promote cell separation (Figueroa‐Cuilan et al, 2021). Indeed, catalytic residues of the active site of DipM At are not conserved, similarly to their homologs in E. coli , EnvC and NlpD.…”
Section: Discussionmentioning
confidence: 99%